The second mini-transplant for unstable mixed chimerism within the first 100 days after hematopoietic stem cell transplant in severe thalassemia - Choeyprasert,W. (Wiley-Blackwell, 2015)
Allogeneic HSCT is the only curative treatment for severe thalassemia disease. MC occurs in one-third of these patients within the first two months after HSCT; this is a major risk factor of graft rejection, especially when RHCs are more than 25%. There is still no consensus for the management of MC, especially in the early phase of HSCT. The DLI has also been described in the treatment of MC following HSCT for hemoglobinopathies, but its success is still not guaranteed. The second HSCT has been an approach used in an attempt to cure patients who reject their graft. Concern about toxicity of conditioning regimen, the second HSCT is usually delayed for at least a year after the first HSCT. We would like to demonstrate the successful use of the second mini-allogeneic HSCT in hemoglobin E/β-thalassemia with evidence of unstable MC in the first 100 days after allogeneic HSCT to prevent further graft loss after allogeneic HSCT. © 2011 John Wiley & Sons A/S.